AN INVESTIGATION OF TEACHING METHODS PRACTICED AT ALJABEL ALGARBY UNIVERSITY (AAU) IN LIBYA - Alfatiemy, Mohamed Moftah; Normawi, Norlia Mat; Yusof, Rohaila Bt (International Business Education Journal, 2011)
Many researchers have conducted studies exploring teaching practices used by accounting educators. However, a limited number of empirical studies have been conducted in Libya. This study which attempted to increase knowledge in such area in Libya had two objectives. The first one aimed to identify the teaching methods that Libyan accounting educators practiced in their use of teaching methods. To achieve this, questionnaires were administered to collect quantitative data of teaching practices at Aljabel Algarby University (AAU), and then analyses were conducted. Findings revealed that respondents reported a high level application of teacher-centered methods than learner-centered methods, by ranking lecture and in-class discussions as the most dominant teaching methods in their classrooms, only four of the 11 teaching methods showed significant relationship with gender, rank and experience; internet, power-point slides, and overhead projector showed significant association with gender, and computer simulations method was significantly associated with Rank and experience. This study helps reads better understand the teaching effectiveness in the Libyan context and provides data for future comparative studies regarding in teaching strategies in accounting.